(2x+1)(ax+b)=(6x^2-5x+c)
Answer:
Step-by-step explanation:
(2x + 1)(ax + b) = 6x² - 5x + c
Expand the left side and put that half into standard form:
2ax² + 2bx + ax + b = 6x² - 5x + c
2ax² + (2b + a)x + b = 6x² - 5x + c
So now look at the x terms. We have "2a" x² on left and 6 x² on right, so:
2a = 6
a = 3
Then look at the x terms, those coefficients will then be equal:
2b + a = -5
2b + 3 = -5
2b = -8
b = -4
and finally, then non-x terms are equal:
b = c
-4 = c
so:
a = 3, b = -4, c = -4
The figure can be separate into a triangle, a rectangle and a trapezium.
Triangle:
Area = 1/2 x base x height
Area = 1/2 x 16 x (25 - 4) = 168 units²
Rectangle:
Area = length x Width
Area = 16 x 4 = 64 units²
Trapezium:
Area = 1/2 (a + b) x h
Area = 1/2 (25 + 15) (10) = 200 units²
Total Area = 200 + 64 + 168 = 432 units²
Answer: 432 units²
Answer:
the answer is 305
Step-by-step explanation:
yes because it did